From electrons to elephants and elections : exploring the role of content and context / Shyam Wuppuluri, Ian Stewart, editors. - Wuppuluri, Shyam; Stewart, Ian, 1945- (Frontiers collection., 2022)
This interdisciplinary text, covering more than six fields, from philosophy and sciences all the way up to the humanities and with contributions from eminent authors, addresses the interplay between content and context, reductionism and holism and their meeting point: the notion of emergence.